In ovo exposure of Eurycoma longifolia extract on the pre-hatched development of chicken embryo (Bangladesh Journal of Animal Science, 2016)
This study was conducted to investigate the effects of in ovo administration of Eurycoma longifolia (Tongkat Ali) extract (TAE) on the survivability and pre hatch development of chicken embryo. A dose response study of 0.1 mg, 1 mg and 10 mg TAE/100g egg on embryo survivability during first 5 days of incubation showed that the 0.1 to 1mg exposures had no effect on embryo survivability, and the lethal dose to kill 50% (LD50) was at around 10 mg. The 0.1 mg exposure was found to be non-lethal to the developing embryo until 19th day of incubation and it also enhanced (p1 mg/100 egg dose is lethal to developing chicken embryo, but the 0.1 mg TAE/100g egg exposure through in ovo injection can be a beneficial strategy to produce heavier and stronger day old chicks.Bang. J. Anim. Sci. 2016. 45 (2): 24-29